2933 Shares Topic: Please help me solve some algebra problems :\?
July 19, 2019 / By Mattie
Question: 1) If c=-3, then 4c2+5c-2= 2) If x is a positive nnumber, then √36x6= In the second one is not 36 mult. to 6, it's letter "x" in 6th power. Kate, release Alt and type 251 on the keypad (not on the top).  Laryn | 2 days ago
1) If c=-3, then 4c2+5c-2= 4 . (-3)² + 5 . (-3) -2 = 4 . 9 - 15 -2 = 36-15-2 = 21-2 = 19 2) sqrt(36= = 6 so √36x6= = 6 . 6 = 36 hope it'll help !!
👍 232 | 👎 2 Originally Answered: How would i solve these algebra problems?
4+7y-10 7y+4-10 7y+-6 7y-6 14x+16xy-17xy+8x 14x+-y+8x 14x-y+8x 14x+8x-y 22x-y Good Luck! Jess
1) If c=-3, then 4c2+5c-2= 36-15-2=19 2) If x is a positive nnumber, then √36x6= 6x*6=36x
👍 100 | 👎 -2 Flori
1) 4(-3)(2)+5(-3)-2 -12(2)+-15-2 -24-17 -43 I'm not totally sure about #2 so I'm not gonna solve that one.
👍 99 | 👎 -6 Dallas
1) 19 2) 12√(3x) How on earth did you get that square root sign? I had to copy and paste you.
👍 98 | 👎 -10 Originally Answered: Help me Solve these Algebra Problems Please.?
I'll put ^ equals to square to simplify everything =) y^ - 24y + 144 = 0 I used the "broom method", so i hope it won't complicate things. (y - 12) | -12y (y - 12) | -12y > y^ + 144 | -24y Therefore, y = 12 (t+7)^ = (t+7)(t+7) [multiply t from the first bracket with (t+7) and 7 from the first bracket with (t+7)] = t(t+7) + 7(t+7) = t^ + 7t + 7t + 49 = t^ + 14t + 49 Do the same with (c-2d)^ (c-2d)^ = c(c-2d) + [(-2d)(c-2d)^] = c^ - 2cd - 2cd + 4d^ = c^ - 4cd + 4d^ Sorry if it's messy =)